Quiet eye training facilitates visuomotor coordination in children with developmental coordination disorder. (May 2015) - Miles, C.A.L.; Wood, G.; Vine, S.J.; Vickers, J.N.; Wilson, M.R.
Highlights: Children with developmental coordination disorder (DCD) show visuomotor deficits. Quiet eye training (QET) teaches individuals to adopt the gaze strategy of expert performers. The current study revealed that children with DCD could effectively respond to QET. Compared to a traditional training intervention, QET individuals revealed a significant improvement in catching quality after training. These benefits remained after a 6 week detraining period. Abstract: Introduction: Quiet eye training (QET) has been shown to be more effective than traditional training (TT) methods for teaching a throw and catch task to typically developing 8–10 yr old children. The current study aimed to apply the technique to children with developmental coordination disorder (DCD). Method: 30 children with DCD were randomly allocated into TT or QET intervention groups. The TT group were taught how to control their arm movements during the throw and catch phases, while the QET group were also taught to fixate a target location on the wall prior to the throw (quiet eye1; QE1), followed by tracking the ball prior to the catch (quiet eye2; QE2). Performance, gaze and motion analysis data were collected at pre/post-training and 6-week retention. Results: The QET group significantly increased QE durations from pre-training to delayed retention (QE1 = +247 ms, QE2 = +19%) whereas the TT group experienced a reduction (QE1 = −74 ms, QE2 = −4%). QET participants showed significant improvement in the quality of their catch attempts and increased elbow flexion at catch compared to the TT group (QET = −28°, TT = −1°). Conclusion: QET changed DCD children's ability to focus on a target on the wall prior to the throw, followed by better anticipation and pursuit tracking on the ball, which in turn led to improved catching technique. QET may be an effective adjunct to traditional instructions, for therapists teaching visuomotor skills to children with DCD.